2016
DOI: 10.1001/jamaoncol.2016.1396
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcomes After Therapy for Hodgkin or Non-Hodgkin Lymphoma Diagnosed During Pregnancy

Abstract: Systemic therapy given for lymphoma after the first trimester of pregnancy is likely safe and results in acceptable maternal and fetal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 13 publications
2
50
2
Order By: Relevance
“…166 Chemotherapy should be avoided during the first trimester because of greater risk of teratogenic effects, which include major congenital malformations, impaired organ function, spontaneous abortions, and fetal death. 167,[170][171][172][173] Although the use of chemotherapy during the second and third trimesters has not been associated with significant teratogenic effects, it may be associated with low birth weight, preterm labor, and intrauterine growth restriction. 157,170,172,[174][175][176] However, a multicenter, prospective case-control study of children born to mothers with cancer (129 cases, 129 controls) showed no significant impact of chemotherapy treatment on cognitive, cardiac, and general development of the offspring.…”
Section: Management Of Cancer During Pregnancymentioning
confidence: 99%
“…166 Chemotherapy should be avoided during the first trimester because of greater risk of teratogenic effects, which include major congenital malformations, impaired organ function, spontaneous abortions, and fetal death. 167,[170][171][172][173] Although the use of chemotherapy during the second and third trimesters has not been associated with significant teratogenic effects, it may be associated with low birth weight, preterm labor, and intrauterine growth restriction. 157,170,172,[174][175][176] However, a multicenter, prospective case-control study of children born to mothers with cancer (129 cases, 129 controls) showed no significant impact of chemotherapy treatment on cognitive, cardiac, and general development of the offspring.…”
Section: Management Of Cancer During Pregnancymentioning
confidence: 99%
“…As a group, lymphoma accounts for 11% of malignancies diagnosed during pregnancy, but given the many presentations at diagnosis and differences in the natural history of each of these entities, little data exists to guide the management of these women. This poses unique challenges to the care of both the mother and the unborn fetus (14,15). Although the goal of treatment is to provide the mother with optimal care while balancing the risks to the fetus, the patient and her providers often encounter many challenges at all stages of management from diagnosis to treatment (14).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, providers are often hesitant to administer rituximab to pregnant patients out of concern for possible fetal harm in the event of an infusion reaction (17). Aside from the treatment itself, timing of treatment is often a challenge faced when treating pregnant women with cancer as, ideally, chemotherapy should be delayed if possible until the second trimester to allow for fetal organogenesis (8,15). In the largest retrospective study of pregnant lymphoma patients treated with non-anti-metabolite chemotherapy, Evens et al noted an overall response rate of 82% and a complete response rate of 64%, which suggested that pregnant women could be successfully treated with chemotherapy and achieve similar outcomes to non-pregnant patients.…”
Section: Methodsmentioning
confidence: 99%
“…However, 1 patient underwent radiotherapy after her pregnancy and the other after an induced abortion. There are other reports of successful systemic therapy for HL and NHL after the 1st trimester [15,16]. This is explained by the fact that chemotherapy is administered after organogenesis and fetal protection is provided by the placental barrier [16].…”
Section: Hematologic Malignanciesmentioning
confidence: 99%